Influence of body mass index on the long-term outcomes of patients with esophageal squamous cell carcinoma who underwent esophagectomy as a primary treatment: A 10-year medical experience. Issue 29 (July 2016) - Ji, Wenhao; Zheng, Weihui; Li, Bo; Cao, Caineng; Mao, Weimin
Abstract : Abstract: We explored the influence of body mass index (BMI) on long-term outcomes in patients with esophageal squamous cell carcinoma (ESCC) who underwent esophagectomy as a primary treatment. BMI is a risk factor for development of esophageal cancer. However, the details of the relationship between BMI and cancer prognosis remains unclear. Patients who underwent esophagectomy as an initial treatment in 2000 to 2009 period were included. The patients were divided into 3 groups according to Asian-specific BMI cut-offs. The associations between BMI and long-term outcomes were explored. This study included 1082 ESCC patients between 2000 and 2009; all the patients underwent esophagectomy. The median overall survival (OS) of the BMI <18.5, 18.5 ⩽ BMI <23, and BMI ≥23 kg/m 2 groups were 21, 24, and 29.5 months, respectively; they differed significantly ( P = 0.005). The 5-year survival rates of the 3 groups were 24.6%, 30.4%, and 35.3%, respectively. Multivariate analysis showed that lower BMI was an independent risk factor for a shorter OS (18.5 ⩽ BMI <23 kg/m 2 vs. BMI ≥23 kg/m 2, hazard ratio [HR] = 1.18; 95% confidence interval [CI] = 1.00–1.40, P = 0.054, BMI <18.5 kg/m 2 vs. BMI ≥23 kg/m 2, HR = 1.38; 95% CI = 1.09–1.75, P = 0.007). The better OS of the BMI ≥23 kg/m 2 patients remained statistically significant in never-smoking patients ( P < 0.05). In conclusion, patients with BMIs ≥23 kg/m 2 experienced better OS, and multivariate analysis further indicated that BMI ≥23 kg/m 2 was an independent predictor of survival. When stratified by smoking status, BMI ≥23 kg/m 2 was still a factor in better OS among never smokers.